Fluorescence‐based soft sensor for at situ monitoring of chinese hamster ovary cell cultures. Issue 8 (16th June 2014) - Ohadi, Kaveh; Aghamohseni, Hengameh; Legge, Raymond L.; Budman, Hector M.
ABSTRACT Multi‐wavelength fluorescence spectroscopy was investigated as a potential tool for use in monitoring key process variables that include: viable and dead cells, recombinant protein, glucose, and ammonia concentrations for Chinese hamster ovary (CHO) cells during cultivation. For the purpose of calibrating the fluorescence‐based empirical model, cells were grown in batch mode with different initial glucose and glutamine concentrations. Spectrofluorometer settings were optimized to ensure reproducibility and accuracy of the acquired spectra. With the purpose of gaining qualitative insight into the evolution of the spectra, the trajectories of individual fluorophore peaks were studied during the cultivation process. Spectral changes related to biomass and secreted proteins were investigated by comparing the spectra at various stages during the downstream processing. A partial least square regression (PLSR) was used to formulate empirical models that related the input data set, i.e., the fluorescence excitation–emission matrix, to the actual state of the system including viable cell and dead cells and recombinant protein, glucose, and ammonia concentrations. The models exhibited accurate prediction ability for the process variables of interest. Biotechnol. Bioeng. 2014;111: 1577–1586. © 2014 Wiley Periodicals, Inc.